Biocatalytic Strategy for Highly Diastereo‐ and Enantioselective Synthesis of 2, 3‐Dihydrobenzofuran‐Based Tricyclic Scaffolds. Issue 30 (24th June 2019) - Vargas, David A.; Khade, Rahul L.; Zhang, Yong; Fasan, Rudi
Abstract: 2, 3‐Dihydrobenzofurans are key pharmacophores in many natural and synthetic bioactive molecules. A biocatalytic strategy is reported here for the highly diastereo‐ and enantioselective construction of stereochemically rich 2, 3‐dihydrobenzofurans in high enantiopurity (>99.9% de and ee), high yields, and on a preparative scale via benzofuran cyclopropanation with engineered myoglobins. Computational and structure‐reactivity studies provide insights into the mechanism of this reaction, enabling the elaboration of a stereochemical model that can rationalize the high stereoselectivity of the biocatalyst. This information was leveraged to implement a highly stereoselective route to a drug molecule and a tricyclic scaffold featuring five stereogenic centers via a single‐enzyme transformation. This work expands the biocatalytic toolbox for asymmetric C–C bond transformations and should prove useful for further development of metalloprotein catalysts for abiotic carbene transfer reactions. Abstract : Forging rings with iron : A biocatalytic strategy for the highly stereoselective cyclopropanation of benzofurans is reported. This enables the efficient construction of enantiopure 2, 3‐dihydrobenzofuran‐based tricyclic scaffolds that are useful for the synthesis of drugs and natural products. Computational and structure–activity studies provide insights into the mechanism of this reaction and the protein‐mediated control of its stereochemical outcome.